Tinjauan Etis Teologis Terhadap Penggunaan Media Game Online di Kalangan Remaja - Saerang, Theovani Andless; Runtuwene, Hendry C. M. (Educatio Christi, 2023)
Online games are games that are currently popular among teenagers. The presence of online games in teenagers' lives has both positive and negative impacts on teenagers' lives. This research aims to conduct a Theological Ethical Review of teenagers in their use of online game media which has an addictive impact and makes teenagers less willing to give themselves to worship because of the influence of online games. The research method that researchers use is a case study with data collection carried out by interviews and direct observation. The results of the research show that in the Worship Fellowship there are still teenagers who are aware of the influence caused by the use of online games and there are also teenagers who are less active and less aware in the Worship Fellowship because of the influence of online gaming media.